PENERAPAN PROGRAM KEAGAMAAN DALAM MEMBANGUN KESEHATAN MENTAL SANTRI PONDOK PESANTREN TAHFIDZUL QUR’AN IBNU RUSYDI CUKIR JOMBANG - Amin Wahono; Ansori, Sholihul (Al Tadib : Jurnal Ilmu Pendidikan, 2026)
This researchhaims to exploreethe effectiveness of religious programs in supporting community mental health. In addition, this study also examines the potential, challenges, and obstaclessthat arise in the9implementation of religious-based programs as an alternative effort in addressing mental health issues. The findings9of this research0are expected to offer recommendations for developing more inclusive and effective religious programs, as well as contribute to the formulation of mental health policies in Indonesia through religious and community-based approaches. Based on the background that has been described, the researcher determines the focus of the study as follows: 1) How is the implementation of religious programs at the Ibnu Rusydi Cukir Jombang Tahfidhul Qur'an Islamic Boarding School? 2) How is the mental health condition of students at the Ibnu Rusydi Cukir Jombang Tahfidhul Qur'an Islamic Boarding School? 3) How do religious programs contribute to the development of students' mental health at the Ibnu Rusydi Cukir Jombang Tahfidhul Qur'an Islamic Boarding School? This studyyrelies on a qualitative9approach through the case0study methodoIt includes dataocollectionntools such asmobservation, interviews, and documentation. The participants in this study consist of the institution's director, Islamic education teachers, and students. The0data0extracted-from the observations and interviews were analyzed using triangulation to ensure0the accuracyuand validity8of the results.